Ceramic polyolefin as well as preparation method and application thereof
By using a specific ratio of polyethylene and ethylene-octene copolymer and ceramicizing powder in ceramicized polyolefins, combined with a preparation method using low-melting-point glass powder and silicate fillers, the problems of insufficient mechanical properties and ceramicizing properties of ceramicized polyolefins have been solved, and high-strength and crack-free ceramic shells have been achieved.
Patent Information
- Application Number
- CN202411587747.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-10
AI Technical Summary
While existing ceramicized polyolefins offer excellent mechanical properties and ceramicization performance, they suffer from insufficient flexibility and strength, and the ceramic shell is prone to cracking.
A ceramicized polyolefin was prepared by using a mixture of polyethylene and ethylene-octene copolymer as the matrix material, a mixture of silica, boron oxide, zinc oxide and magnesium oxide as the ceramicizing powder, and adding low-melting-point glass powder and silicate fillers through a mixing and extrusion process.
The prepared ceramicized polyolefin has excellent tensile strength and elongation at break, and the ceramic shell is intact and crack-free, making it suitable for applications such as wires and cables.
Smart Images

Figure BDA0005124995080000061 
Figure BDA0005124995080000071 
Figure BDA0005124995080000072
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional materials, and in particular to a ceramic polyolefin and a preparation method and application thereof. Background Art
[0002] Ceramic polyolefin is a polymer material prepared by adding ceramic additives to polyolefin resin. It has the characteristics of both polyolefin resin and ceramic. After being burned, it can be quickly vitrified to form a ceramic shell, which has good fire prevention and heat insulation effects. It is widely used in wires and cables, fire blocking, rail transit and other fields.
[0003] In order to adapt to different usage scenarios and installation conditions, ceramic polyolefin is usually required to have excellent mechanical properties. However, ceramic polyolefin in the prior art often cannot take into account both excellent mechanical properties and porcelain properties, such as insufficient flexibility and strength, or the ceramic shell is prone to cracking. Summary of the invention
[0004] The object of the present invention is to provide a ceramic polyolefin and a preparation method and application thereof. The ceramic polyolefin provided by the present invention has both excellent mechanical properties and porcelain properties, wherein the tensile strength and elongation at break are high, and the ceramic shell is complete.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a ceramic polyolefin, which comprises the following preparation raw materials by weight:
[0007] 40-60 parts of a polyolefin resin, wherein the polyolefin resin is a mixture of polyethylene and ethylene-octene copolymer;
[0008] 40-60 parts of porcelain powder, wherein the porcelain powder is a mixture of silicon dioxide, boron oxide, zinc oxide and magnesium oxide;
[0009] 20 to 40 parts of low-melting-point glass powder, wherein the melting point of the low-melting-point glass powder is 400 to 600° C.;
[0010] 15-60 parts of silicate filler;
[0011] Antioxidant 0.1 to 3 parts.
[0012] Preferably, the mass ratio of polyethylene to ethylene-octene copolymer in the polyolefin resin is 1 to 5:1.
[0013] Preferably, the polyethylene is linear low density polyethylene.
[0014] Preferably, the mass ratio of silicon dioxide, boron oxide, zinc oxide and magnesium oxide in the porcelain powder is 1-1.5:2-3:1-2:1-1.8.
[0015] Preferably, the low-melting-point glass powder includes one or more of silicate glass powder, borate glass powder and phosphate glass powder.
[0016] Preferably, the silicate filler includes one or more of kaolin, wollastonite, mica powder and montmorillonite.
[0017] Preferably, the silicate filler is a mixture of kaolin, wollastonite and mica powder, and the mass ratio of kaolin, wollastonite and mica powder in the silicate filler is 1:1:1.
[0018] The present invention provides a method for preparing the ceramic polyolefin described in the above technical solution, comprising the following steps:
[0019] The ceramic polyolefin is obtained by mixing polyolefin resin, ceramic powder, low melting point glass powder, silicate filler and antioxidant, kneading and extruding in sequence.
[0020] Preferably, the temperature of the banburying is 150-160°C; the temperature of the extrusion is 120-150°C.
[0021] The present invention provides the use of the ceramic polyolefin described in the above technical solution or the ceramic polyolefin prepared by the preparation method described in the above technical solution as a fireproof and heat-insulating material.
[0022] The present invention provides a ceramic polyolefin, which includes the following raw materials by weight: 40-60 parts of polyolefin resin, which is a mixture of polyethylene and ethylene-octene copolymer; 40-60 parts of ceramic powder, which is a mixture of silicon dioxide, boron oxide, zinc oxide and magnesium oxide; 20-40 parts of low-melting glass powder, which has a melting point of 400-600°C; 15-60 parts of silicate fillers; and 0.1-3 parts of antioxidants. The present invention uses polyethylene and ethylene-octene copolymer as a matrix material to prepare ceramic polyolefin, uses silicon dioxide, boron oxide, zinc oxide and magnesium oxide as ceramic powder, and adds low-melting glass powder and silicate fillers, so that the prepared ceramic polyolefin has both excellent mechanical properties and ceramic properties. The results of the test example show that the ceramic polyolefin provided by the present invention has excellent tensile strength and elongation at break, and the ceramic shell is complete. DETAILED DESCRIPTION
[0023] The present invention provides a ceramic polyolefin, which comprises the following preparation raw materials by weight:
[0024] 40-60 parts of a polyolefin resin, wherein the polyolefin resin is a mixture of polyethylene and ethylene-octene copolymer;
[0025] 40-60 parts of porcelain powder, wherein the porcelain powder is a mixture of silicon dioxide, boron oxide, zinc oxide and magnesium oxide;
[0026] 20 to 40 parts of low-melting-point glass powder, wherein the melting point of the low-melting-point glass powder is 400 to 600° C.;
[0027] 15-60 parts of silicate filler;
[0028] Antioxidant 0.1 to 3 parts.
[0029] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art.
[0030] In terms of mass fraction, the raw material for preparing the ceramic polyolefin of the present invention includes 40 to 60 parts of polyolefin resin, specifically 40 parts, 45 parts, 50 parts, 55 parts, 57 parts, 59 parts or 60 parts. In the present invention, the polyolefin resin is a mixture of polyethylene (PE) and ethylene-octene copolymer (POE); the present invention uses a mixture of PE and POE as a matrix material to prepare ceramic polyolefin, which can improve the toughness of ceramic polyolefin and is beneficial to improving its impact strength and elongation at break. In the present invention, the mass ratio of polyethylene to ethylene-octene copolymer in the polyolefin resin is preferably 1 to 5:1, specifically 1:1, 2:1, 3:1, 4:1 or 5:1; the present invention preferably controls the mass ratio of PE to POE within the above range, which can make the ceramic polyolefin have good toughness and strength, and is beneficial to improving the dispersion effect of each component. In the present invention, the polyethylene is preferably a linear low-density polyethylene (LLDPE), and the density of the linear low-density polyethylene of the present invention is preferably 0.918 to 0.935 g / cm 3 The melting point is preferably 110-125°C, and its molecular weight distribution is narrow; the present invention preferably uses linear low-density polyethylene, which has higher tensile strength and environmental stress cracking resistance than high-density polyethylene (HDPE) and low-density polyethylene (LDPE), and its compounding with POE is more conducive to improving the tensile strength and environmental stress cracking resistance of ceramic polyolefins.
[0031] Based on the mass fraction of the polyolefin resin, the raw material for preparing the ceramic polyolefin of the present invention includes 40 to 60 parts of ceramic powder, specifically 40 parts, 43 parts, 45 parts, 47 parts, 50 parts, 55 parts or 60 parts. In the present invention, the ceramic powder is a mixture of silicon dioxide, boron oxide, zinc oxide and magnesium oxide; the present invention uses a mixture of silicon dioxide, boron oxide, zinc oxide and magnesium oxide as ceramic powder to prepare polyolefin resin, which can significantly improve the mechanical strength and hardness of the ceramic polyolefin, which is conducive to maintaining excellent physical properties in a high temperature environment. In the present invention, the mass ratio of silicon dioxide, boron oxide, zinc oxide and magnesium oxide in the ceramic powder is preferably 1-1.5:2-3:1-2:1-1.8, and more preferably 1.02:2.34:1.12:1.08; the particle size of the ceramic powder is preferably 5-15 μm; the present invention preferably controls the mass ratio of silicon dioxide, boron oxide, zinc oxide and magnesium oxide and the particle size of the ceramic powder within the above range, so that the grains in the product obtained after sintering the ceramic polyolefin are finer and more evenly distributed, the combination is more tightly, and the pore distribution is more uniform, which is beneficial to improve the density of the ceramic polyolefin and the porcelain strength after sintering.
[0032] Based on the mass fraction of the polyolefin resin, the raw material for preparing the ceramic polyolefin of the present invention includes 20 to 40 parts of low-melting glass powder, which can be specifically 20 parts, 25 parts, 38 parts, 30 parts, 32 parts, 35 parts or 40 parts. In the present invention, the melting point of the low-melting glass powder is 400 to 600°C, preferably 400 to 500°C. The present invention uses low-melting glass powder to prepare ceramic polyolefin, which can reduce the ceramic forming temperature, which is conducive to rapid melting when encountering high temperature to form a liquid phase material, thereby promoting the ceramic process. In the present invention, the low-melting glass powder preferably includes one or more of silicate glass powder, borate glass powder and phosphate glass powder, more preferably silicate glass powder, borate glass powder or phosphate glass powder; the particle size of the low-melting glass powder is preferably 5 to 12 μm. In the present invention, the low-melting-point glass powder is used as a flux, and its melting point is relatively low. When the ceramic polyolefin is sintered, the decomposition residue of the polyolefin resin reacts with the liquid phase material produced by the melting of the low-melting-point glass powder and the silicate filler to form a ceramic body. The present invention preferably uses the low-melting-point glass powder with the above-mentioned particle size, which is beneficial to improving the fluidity and uniformity of the ceramic polyolefin.
[0033] Based on the mass fraction of the polyolefin resin, the raw material for preparing the ceramic polyolefin of the present invention includes 15 to 60 parts of silicate fillers, specifically 15 parts, 17 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts or 60 parts. In the present invention, the silicate filler preferably includes one or more of kaolin, wollastonite, mica powder and montmorillonite, more preferably a mixture of kaolin, wollastonite and mica powder; when the silicate filler is a mixture of kaolin, wollastonite and mica powder, the mass ratio of kaolin, wollastonite and mica powder in the silicate filler is preferably 1:1:1; the particle size of the silicate filler is preferably 5 to 13 μm. The present invention preferably adopts the above-mentioned formula and silicate filler of particle size, which can improve the hardness, strength and thermal stability of ceramic polyolefin and promote the ceramicization process. When the ceramic polyolefin is sintered, the silicate filler reacts with the liquid phase material produced by the melting of the polyolefin decomposition residue and the low-melting point glass powder to form a ceramic body; and the silicate filler can improve the flame retardant properties of the ceramic polyolefin, which is conducive to promoting its application in the fields of fire prevention and fire resistance.
[0034] Based on the mass fraction of the polyolefin resin, the raw material for preparing the ceramic polyolefin of the present invention includes 0.1 to 3 parts of antioxidant, specifically 0.1, 0.2, 0.3, 0.4, 0.5, 1, 1.5, 2, 2.5 or 3 parts. In the present invention, the antioxidant is preferably one or more of antioxidant 1010, antioxidant 1098, antioxidant 168 and antioxidant 626, more preferably a mixture of antioxidant 1010 and antioxidant 168; when the antioxidant is a mixture of antioxidant 1010 and antioxidant 168, the mass ratio of antioxidant 1010 to antioxidant 168 in the antioxidant is preferably 1.5 to 2.5:1, more preferably 2:1.
[0035] In the embodiment of the present invention, the density of the ceramic polyolefin is 1.49-1.53 g / cm 3 The tensile strength is 8.9-11.1MPa, the elongation at break is 456-702%, the breakdown strength is 29-30MV / m, the ceramic bending strength is 12.1-12.7MPa, and the ceramic formed after sintering has a complete appearance without cracking or expansion.
[0036] The present invention provides a method for preparing the ceramic polyolefin described in the above technical solution, comprising the following steps:
[0037] The ceramic polyolefin is obtained by mixing polyolefin resin, ceramic powder, low melting point glass powder, silicate filler and antioxidant, kneading and extruding in sequence.
[0038] The present invention mixes polyolefin resin, porcelain powder, low melting point glass powder, silicate filler and antioxidant for internal kneading to obtain internal kneading material. In the present invention, the internal kneading temperature is preferably 150-160°C, more preferably 150-155°C; the time is preferably 15-25min, more preferably 20min; the rotation speed is preferably 40-60rpm, more preferably 50rpm. In an embodiment of the present invention, the internal kneading is specifically carried out in a pressure internal mixer.
[0039] After obtaining the internally mixed material, the present invention extrude the internally mixed material. In the present invention, the extrusion temperature is preferably 120-150°C, more preferably 125-145°C, further preferably 130-140°C, and further preferably 130-135°C; the rotation speed is preferably 90-110rpm, more preferably 100rpm. In an embodiment of the present invention, the extrusion is specifically carried out in a single-screw extruder; the extrusion temperature is specifically the screw temperature of the single-screw extruder, and the extrusion rotation speed specifically refers to the screw rotation speed of the single-screw extruder.
[0040] After the extrusion, the present invention preferably further comprises pelletizing, cooling and drying the obtained extruded material in sequence to obtain the ceramic polyolefin. The present invention has no special limitation on the pelletizing, cooling and drying, and processes well known to those skilled in the art can be used.
[0041] The preparation method of ceramic polyolefin provided by the invention has simple process and low production cost.
[0042] The present invention provides the use of the ceramic polyolefin described in the above technical solution or the ceramic polyolefin prepared by the preparation method described in the above technical solution as a fireproof and heat-insulating material. In the present invention, the fireproof and heat-insulating material can specifically be a fireproof and heat-insulating material in wires and cables. The present invention does not specifically limit the application method of the ceramic polyolefin, and can adopt a method familiar to those skilled in the art. The ceramic polyolefin described in the present invention has excellent mechanical and electrical properties, can be sintered to form a complete and hard ceramic shell after being burned by an open flame, can withstand vibrations of a certain intensity, and will not crack or fall off after being rained on, and can meet the use requirements of wires and cables.
[0043] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] The sources and indicators of some raw materials in the following examples and comparative examples are as follows:
[0045] Polyethylene (PE) is linear low-density polyethylene (LLDPE), purchased from EQUATE, Kuwait, model EFDC-7050;
[0046] Ethylene-octene copolymer (POE) was purchased from Mitsui Chemicals, model number PN-3560;
[0047] Ethylene-vinyl acetate copolymer (EVA) was purchased from DuPont, model Elvax260;
[0048] The particle size of the porcelain powder is 5 to 15 μm;
[0049] The particle size of the low melting point glass powder is 5 to 12 μm;
[0050] The particle size of the silicate filler is 5 to 13 μm.
[0051] Example 1
[0052] In parts by weight, the raw materials for preparing ceramic polyolefin in this embodiment are as follows:
[0053] 60 parts of polyolefin resin, wherein the polyolefin resin is a mixture of PE and POE in a mass ratio of 2:1;
[0054] 45 parts of porcelain powder, wherein the porcelain powder is a mixture of silicon dioxide, boron oxide, zinc oxide and magnesium oxide in a mass ratio of 1.02:2.34:1.12:1.08;
[0055] 30 parts of low-melting-point glass powder, wherein the low-melting-point glass powder is phosphate glass powder with a melting point of 400° C.;
[0056] 15 parts of silicate filler, wherein the silicate filler is a mixture of kaolin, wollastonite and mica powder in a mass ratio of 1:1:1;
[0057] 0.3 parts of antioxidant, which is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 2:1.
[0058] The preparation method of ceramic polyolefin in this embodiment is as follows:
[0059] Put polyolefin resin, porcelain powder, low melting point glass powder, silicate filler and antioxidant in a pressure mixer, and mix them for 20 minutes at a temperature of 150° C. and a rotation speed of 50 rpm to obtain a mixed material;
[0060] The mixed material is added from the feed port of a single-screw extruder, extruded under the conditions of a screw temperature of 130° C. and a screw speed of 100 rpm, and then pelletized, cooled and dried in sequence to obtain the ceramic polyolefin.
[0061] Examples 2 to 3 and Comparative Examples 1 to 9
[0062] Ceramic polyolefin was prepared by referring to the method of Example 1, except for the formula, as shown in Table 1.
[0063] Table 1 is the formula of ceramic polyolefin in the examples and comparative examples, wherein the parts involved are parts by mass and the component ratios are mass ratios; the types of raw materials and preparation methods not mentioned are all referred to in Example 1.
[0064] Table 1 Formulations of ceramic polyolefins in Examples and Comparative Examples
[0065]
[0066]
[0067] Test Example 1
[0068] The ceramic polyolefin prepared in the embodiment and the comparative example was subjected to performance tests. The test results are shown in Table 2, wherein the tensile strength was tested according to the GB / T 1040 method, the elongation at break was tested according to the GB / T 1040 method, the breakdown strength was tested according to the GB / T 1408 method, the ceramic bending strength was tested according to the GB / T 6569-2006 method, the density was tested according to the GB / T 6569-2006 method, and the ceramic appearance was visually inspected.
[0069] Table 2 Performance test results of ceramic polyolefins prepared in Examples and Comparative Examples
[0070]
[0071]
[0072] It can be seen from Table 2 that the ceramic polyolefin materials prepared in Examples 1 to 2 have good tensile strength and elongation at break, and the ceramic shell is intact and hard; as shown in Example 3, increasing the amount of POE will reduce the tensile strength to a certain extent and increase the elongation at break.
[0073] In addition, it can be seen from Table 2 that excessive use of polyolefin resin in Comparative Example 1 will lead to a decrease in the density of the ceramic polyolefin material, which will in turn lead to a decrease in the ceramic strength (i.e., ceramic bending strength). In Comparative Example 2, POE is not used, only PE is used, and the elongation at break decreases seriously. In Comparative Example 3, the polyolefin resin is compounded with PE and EVA, and the use of EVA will cause a decrease in tensile strength and elongation at break. In Comparative Example 4, ceramic powder is not used, and the ceramic strength is poor. In Comparative Example 5, low-melting point glass powder is not used, the appearance of the ceramic is poor, and the surface cracks are large. In Comparative Example 6, boron oxide is not used, and the ceramic bending strength decreases. In Comparative Example 7, zinc oxide is not used, and there is a slight expansion after ceramic formation. In Comparative Example 8, magnesium oxide is not used, and the tensile strength decreases.
[0074] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A ceramic polyolefin, characterized in that: The preparation materials include the following by weight: 40-60 parts of a polyolefin resin, wherein the polyolefin resin is a mixture of polyethylene and ethylene-octene copolymer; 40-60 parts of porcelain powder, wherein the porcelain powder is a mixture of silicon dioxide, boron oxide, zinc oxide and magnesium oxide; 20 to 40 parts of low-melting-point glass powder, wherein the melting point of the low-melting-point glass powder is 400 to 600° C.; 15-60 parts of silicate filler; Antioxidant 0.1 to 3 parts.
2. The ceramic polyolefin according to claim 1, characterized in that: The mass ratio of polyethylene to ethylene-octene copolymer in the polyolefin resin is 1 to 5:
1.
3. The ceramic polyolefin according to claim 1 or 2, characterized in that: The polyethylene is linear low density polyethylene.
4. The ceramic polyolefin according to claim 1, characterized in that: The mass ratio of silicon dioxide, boron oxide, zinc oxide and magnesium oxide in the porcelain powder is 1-1.5:2-3:1-2:1-1.
8.
5. The ceramic polyolefin according to claim 1, characterized in that: The low melting point glass powder includes one or more of silicate glass powder, borate glass powder and phosphate glass powder.
6. The ceramic polyolefin according to claim 1, characterized in that: The silicate filler includes one or more of kaolin, wollastonite, mica powder and montmorillonite.
7. The ceramic polyolefin according to claim 6, characterized in that: The silicate filler is a mixture of kaolin, wollastonite and mica powder, and the mass ratio of kaolin, wollastonite and mica powder in the silicate filler is 1:1:
1.
8. The method for preparing ceramic polyolefin according to any one of claims 1 to 7, characterized in that: The following steps are involved: The ceramic polyolefin is obtained by mixing polyolefin resin, ceramic powder, low melting point glass powder, silicate filler and antioxidant, kneading and extruding in sequence.
9. The preparation method according to claim 8, characterized in that: The temperature of the banburying is 150-160°C; the temperature of the extrusion is 120-150°C.
10. Use of the ceramic polyolefin according to any one of claims 1 to 7 or the ceramic polyolefin prepared by the preparation method according to claim 8 or 9 as a fireproof and heat-insulating material.
Citation Information
Patent Citations
Ceramic polyolefin and preparation method thereof
CN112300480A
Cited By
Enameled round graphene aluminum alloy winding wire and production process thereof
CN120376231A
An enameled round graphene aluminum alloy winding wire and a production process thereof
CN120376231B
Polyolefin composite material as well as preparation method and application thereof
CN122011561A
Novel heat-insulating, flame-retardant, fire-resistant and high-temperature-resistant material and application thereof
CN122897692A